92.8k views
25 votes
Use any order, any grouping to write an equivalent expression: 3(2x) + 4y(5) + (4 x 2 x z)

1 Answer

9 votes

Answer:

We conclude that the equivalent expression is:


3\left(2x\right)+4y\left(5\right)+\left(4* \:2z\right)=6x+20y+8z

Explanation:

Given the expression


3\left(2x\right)+4y\left(5\right)+\left(4* \:2z\right)

Remove parentheses: (a) = a


=3* \:2x+4* \:5y+4* \:2z

Multiply the numbers: 3 × 2 = 6


=6x+4* \:5y+4* \:2z

Multiply the numbers: 4 × 5 = 20


=6x+20y+4* \:2z

Multiply the numbers: 4 × 2 = 8


=6x+20y+8z

Thus, we conclude that the equivalent expression is:


3\left(2x\right)+4y\left(5\right)+\left(4* \:2z\right)=6x+20y+8z

User Editha
by
5.1k points